1993
DOI: 10.1126/science.8211186
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Behavior Associated with a Point Mutation in the Structural Gene for Monoamine Oxidase A

Abstract: Genetic and metabolic studies have been done on a large kindred in which several males are affected by a syndrome of borderline mental retardation and abnormal behavior. The types of behavior that occurred include impulsive aggression, arson, attempted rape, and exhibitionism. Analysis of 24-hour urine samples indicated markedly disturbed monoamine metabolism. This syndrome was associated with a complete and selective deficiency of enzymatic activity of monoamine oxidase A (MAOA). In each of five affected male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
747
2
26

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,472 publications
(812 citation statements)
references
References 34 publications
25
747
2
26
Order By: Relevance
“…These findings are consistent with abnormal behavior in men of the Dutch family with heritable lack of MAO A, showing disproportionate to the provocation impulsive aggression in response to psychosocial stress [Brunner et al, 1993].…”
Section: Discussionsupporting
confidence: 85%
“…These findings are consistent with abnormal behavior in men of the Dutch family with heritable lack of MAO A, showing disproportionate to the provocation impulsive aggression in response to psychosocial stress [Brunner et al, 1993].…”
Section: Discussionsupporting
confidence: 85%
“…Aggression alleles per se (in other words, influencing aggression but nothing else) probably do not exist, but there are some alleles that have been associated with aggression or aggression-related disorders. 2 For example, a point mutation in the monoamine oxidase A gene (MAO-A is an enzyme that breaks down 5-HT, NE, and DA) was described in a Dutch family with borderline mental retardation and intermittent explosive aggression (Brunner, Nelen, van Zandvoort, et al, 1993;Brunner, Nelen, Breakefield, Ropers, & van Oost, 1993). Although this appears to be an extremely rare condition, recent studies have shown that polymorphisms in the MAO-A gene may also be important in the etiology of antisocial behavior, in combination with environmental factors such as exposure to maltreatment in childhood (Caspi et al, 2002).…”
Section: The 5-ht 1b Receptor and Serotonergic Genesmentioning
confidence: 99%
“…Loss of function of MAOA caused by a deficiency in the MAOA gene or decreased activity of the enzyme caused by a MAOA promoter polymorphism is associated with violent, criminal, or impulsive behavior in humans (Brunner et al, 1993). MAOA knockout mice also showed increased aggressive behavior where the brain NE and serotonin concentrations were markedly increased (Cases et al, 1995;Daniel et al, 2001).…”
Section: Cumulative Revolution Numbers/12hrmentioning
confidence: 99%